Antibacterial activity of plants that are used in the treatment of heartwater in livestock and the isolation and identification of bioactive compounds from Petalidium Oblongifolium and Ipomoea adenioides - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2013)
Thesis (PhD (Botany))--University of Pretoria, 2007.